2021
DOI: 10.1186/s12905-021-01517-9
|View full text |Cite
|
Sign up to set email alerts
|

The trends of women’s autonomy in health care decision making and associated factors in Ethiopia: evidence from 2005, 2011 and 2016 DHS data

Abstract: Background Women's autonomy in health care decision-making is very crucial for the well-being of women themselves, their children, and the entire family members. Although studying the issue is significant to take proper interventions, the issue is not studied at a nationwide level in Ethiopia. Accordingly, this population-based nationwide study was aimed at assessing the trends of women’s autonomy in health care decision-making and its associated factors in Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
7
25
0
Order By: Relevance
“…This study shows that women’s age was significantly associated with women’s decision-making autonomy regarding maternal healthcare services. Accordingly, it is found that women’s autonomy to make their own health-related decisions increases with age, which is in line with a study done using the EDHS 25. Several studies in low-income and middle-income countries have also indicated that women’s increasing age has a favourable impact on their autonomy to make health-related decisions on their own 2.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This study shows that women’s age was significantly associated with women’s decision-making autonomy regarding maternal healthcare services. Accordingly, it is found that women’s autonomy to make their own health-related decisions increases with age, which is in line with a study done using the EDHS 25. Several studies in low-income and middle-income countries have also indicated that women’s increasing age has a favourable impact on their autonomy to make health-related decisions on their own 2.…”
Section: Discussionsupporting
confidence: 84%
“…Accordingly, it is found that women’s autonomy to make their own health-related decisions increases with age, which is in line with a study done using the EDHS. 25 Several studies in low-income and middle-income countries have also indicated that women’s increasing age has a favourable impact on their autonomy to make health-related decisions on their own. 2 Other studies have also demonstrated the influence of age on women’s autonomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides this, this finding is lower than the study done in part of Ethiopia like Wollaita and Dawro zones (58.4%) [ 19 ],(Ambo town (55.6%) [ 20 ], Debretabor (75.1%) [ 22 ], analysis from the Ethiopian demographic health survey(EDHS) 2011 (54%) [ 33 ], Basoliben district (80%) [ 34 ] and further analysis of the EDHS 2016 reported that (81.6%) of women had higher decision-making autonomy [ 35 ].…”
Section: Discussionmentioning
confidence: 99%